Circ_0061825 Acts as a miR-593-3p Sponge to Promote Breast Cancer Progression by Regulating FGFR3 Expression [Retraction] - Xie J; Wan Y; Zhang M; Jin Z; Yao Y (Cancer Management and Research)
Xie J, Wan Y, Zhang M, Jin Z, Yao Y. Cancer Manag Res. 2020;12:11243–11255. We, the Editors and Publisher of the journal Cancer Management and Research have retracted the published article. After publication, concerns were raised by a third party about the integrity of the data in Figure 2 and Figure 4 of the article. Further investigation conducted by the Journal and Publisher confirmed duplicate image panels representative of different treatment conditions present in both Figure 2 and Figure 4 of the article. The authors have not responded to the queries raised by the Journal and Publisher. As verifying the validity of published work is core to the integrity of the scholarly record, we are therefore retracting the article. The corresponding author listed in this publication has been informed. We have been informed in our decision-making by our editorial policies and the COPE guidelines. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as ‘Retracted’.